Pattern of Deep Bite among Orthodontic Patients at Dhaka Dental College and Hospital (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Aims: To assess the pattern of deep bite of orthodontic patients.Material and methods: In this cross sectional study, a total number of 200 sets of pretreatment study cast of patients selected from model store of Orthodontics Department in Dhaka Dental College & Hospital, Mirpur-14, Dhaka-1206, Bangladesh.Results: The study finding show the percentage distribution were as follows, 1% of the sample had open bite, 38.5 % of the sample had normal value of incisor overbite, while 60%patients showed varying values of deep bite. As far as the distribution of these 121 patients in different categories of deep bite is concerned. Maximum number of patients; 50% of these were having mild degree of deep bite while only6.5% showed moderate degree of deep bite and 3.5% showed full coverage of lower incisor crowns.Conclusion: The conclusion that can be drawn from this study is that the commonest overbite relationship in the Bangladeshi sample is the mild overbite (50% patients). Moderate and severe deep bite malocclusions are less prevalent but nearly of the same percentage distribution. In all categories of deep bite, female to male ratio was higher.Ban J Orthod & Dentofac Orthop, April 2014; Vol-4 (1-2), P.16-19